The Intra- and Intercellular Movement of Melon necrotic spot virus (MNSV) Depends on an Active Secretory Pathway - Ainhoa Genovés; Jose Antonio Navarro; Vicente Pallás (Molecular Plant-Microbe Interactions, 2010)
Plant viruses hijack endogenous host transport machinery to aid their intracellular spread. Here, we study the localization of the p7B, the membrane-associated viral movement protein (MP) of the Melon necrotic spot virus (MNSV), and also the potential involvement of the secretory pathway on the p7B targeting and intra- and intercellular virus movements. p7B fused to fluorescent proteins was located throughout the endoplasmic reticulum (ER) at motile Golgi apparatus (GA) stacks that actively tracked the actin microfilaments, and at the plasmodesmata (PD). Hence, the secretory pathway inhibitor, Brefeldin A (BFA), and the overexpression of the GTPase-defective mutant of Sar1p, Sar1[H74L], fully retained the p7B within the ER, revealing that the protein is delivered to PD in a BFA-sensitive and COPII-dependent manner. Disruption of the actin cytoskeleton with latrunculin B led to the accumulation of p7B in the ER, which strongly suggests that p7B is also targeted to the cell periphery in an actin-dependent manner. Remarkably, the local spread of the viral infection was significantly restricted either with the presence of BFA or under the overexpression of Sar1[H74L], thus revealing the involvement of an active secretory pathway in the intracellular movement of MNSV. Overall, these findings support a novel route for the intracellular transport of a plant virus led by the GA.